Evaluation of Sagittal Change in the Maxilla and Incisor Inclination Following Rapid Palatal Expansion Using Cone Beam Computerized Tomography - Pasha, Hajra; Anwar, Ayesha; Bangash, Azhar Ali (Pakistan Armed Forces Medical Journal, 2022)
Objective: To measure the sagittal changes in the maxilla via angular change in point A with Sella Nasion plane and incisor to palatal plane before (T1) and after (T2) rapid palatal expansion with bonded expander. Study Design: Quasi-experimental study. Place and Duration of Study: Armed Forces Institute of Dentistry Rawalpindi Pakistan, from Feb 2017 from Jan 2018. Methodology: 30 patients both male and female presenting to orthodontics department AFID between the ages of 9 and 12 years, with transverse maxillary deficiency were given a bonded hyrax appliance with an activation schedule of 2 turns per day, the retention period was 2 months followed by further retention with a removable plate. Two cone beam computerized tomography evaluations were done. One pre-expansion (T1) and the other after 2 months of retention (T2). Results: 30 children 16 males (53%) and 14 females (47%) with a mean age of 11.03 ± 0.76 years were studied showing that from pre-treatment to post-treatment Sella Nasion point A value changed insignificantly from 77.03 ± 2.81 to 77.2 ± 3.02and 1 to palatal plane changed insignificantly from 111.82 ± 5.74 to 110.8 ± 5.80. Paired sample t-test results confirmed the statistically insignificant change in Sella Nasion point A and 1to Palatal Plane. Conclusion: Following rapid palatal expansion with a bonded expander in growing patients the change in maxillary location in the sagittal dimension and the change in inclination of incisor to palatal plane following expansion was insignificantly affected statistically and hence clinically.